2017
DOI: 10.21475/ajcs.17.11.11.pne461
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the genetic diversity of dessert watermelon (Citrullus lanatus var. lanatus) landrace collections of South Africa using SSR markers

Abstract: Dessert watermelon landraces could provide useful germplasm sources for commercial watermelon breeding and/or conservation. This study assessed the genetic diversity present among dessert watermelon landrace collections of South Africa using simple sequence repeat (SSR) markers. Thirty one diverse dessert watermelon landraces were genotyped using 10 polymorphic SSR markers. A total of 94 alleles were amplified among the sampled population. The number of alleles ranged from 2 to 19 with a mean of 9.4 per locus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In this study, gene flow (Nm) among 68 watermelon accessions was 4.43, suggesting a high genetic introgression. Previous studies reported similar results with a low genetic differentiation value and high gene flow among watermelon [39,40]. Gene flow <1 is considered to be low whereas Nm = 1 is considered to be moderate [41].…”
Section: Discussionmentioning
confidence: 53%
“…In this study, gene flow (Nm) among 68 watermelon accessions was 4.43, suggesting a high genetic introgression. Previous studies reported similar results with a low genetic differentiation value and high gene flow among watermelon [39,40]. Gene flow <1 is considered to be low whereas Nm = 1 is considered to be moderate [41].…”
Section: Discussionmentioning
confidence: 53%
“…SSR markers can be used effectively in population genetics and gene mapping studies because of their advantages as an informative marker system including requiring small amounts of DNA, being codominant and stable, being abundant and scattered throughout the genome, being reproducible and suitable for automation, and having a high level of polymorphism 18 . The SSR technique has successfully been used in the assessment of genetic diversity in cucurbit species such as pumpkin/squash 19 22 , bowler 23 , snake melon 24 watermelon 25 , 26 , bitter melon 27 , cucumber 28 . The rate of foreign fertilization in pumpkin is very high.…”
Section: Introductionmentioning
confidence: 99%
“…The citron watermelon root architecture has a primary taproot and several lateral roots [ 6 ]. Genetic variability has been reported in the species for morphological traits, including RSA traits [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Using a genetically diverse population of citron watermelon accessions collected and grown in the drier parts of South Africa by small-holder farmers, Mandizvo et al [ 26 ] observed variability in the estimated root percentage, taproot length and root dry mass among the accessions after exposure to drought stress.…”
Section: Introductionmentioning
confidence: 99%